Navigating the gerontechnological frontier: Innovations and challenges in the care field - Belkais Kebir; Kristina Barczik (Gerontechnology)
Background: In the coming decades, the population of individuals aged 65 and above is projected to experience a notable surge. This demographic transition demands novel approaches to improve and transform elder care practices using emerging gerontechnologies. Objective: This article presents a comprehensive analysis of the gerontechnology domain and its applications in elderly care. Furthermore, it aims to improve understanding in the care field and promote the advancement of elder care by utilizing evidence-based strategies and identifying research priorities. Method: This article is based on a systematic review of the literature published between January 2022 and December 2023, which was conducted by employing the PRISMA methodology, and reputable databases such as PsycInfo, PubMed, IEEE Xplore, and CINAHL were used to compile the data. Results: This research aims to categorize existing technologies to reveal a diverse array of products and technologies to address the distinct needs of the elderly. Their implementation within the care sector is given particular attention in order to emphasize innovative approaches to enhance the quality of senior care. Moreover, the research highlights the current scientific challenges, limitations and research gaps in the development and integration of advanced technologies that are observed within the field of gerontechnology. This enables the researchers to improve the existing knowledge of the field and offers a comprehensive foundation for directing future research efforts and technological innovations. Conclusion: This framework is intended to serve as a strategic guide for advancing the integration of emerging technologies into elder care practices. This paper provides valuable insights for researchers, practitioners, and policymakers by presenting a thorough analysis of the current state of gerontechnology. It highlights critical scientific challenges as well as strategic recommendations for addressing these issues.